Properties of lightweight fibrous materials made using a foam-forming technique - Burke, Steven (Trinity College Dublin. School of Physics. Discipline of Physics, 2021)
This thesis concerns the production and characterisation of foam-formed fibrous materials made from wood, peat fibres and spent grain. Such materials might find commercial applications for insulating purposes when produced at low density, or replace cardboard when produced at higher densities. The materials are produced by axially shearing a fibre-laden aqueous solution to which a surfactant has been added. The dispersion is then poured into a drainage vessel, where the liquid drains via gravity resulting in a lightweight fibrous sample. The addition of fibres to an aqueous foam changes its properties. By adding fibres, a foam?s lifetime can be greatly extended. Furthermore, the fibres place an upper limit on the average bubble size by arresting bubble growth during coarsening. The influence of fibre concentration and liquid content of a foam-fibre dispersion is explored. We report a minimum fibre concentration required for sample stability. We show how both fibre concentration and the liquid content of the dispersion affects sample density. Uniaxial compression testing shows that the compressive modulus scales linearly with sample density. The liquid content of the dispersion can also be used to tune the sample compressive strength, when compressed in all three axial directions. The compressive modulus is increased by a factor of up to seven, just by changing the liquid content of the dispersion from 25% to 50% (with no change to sample density). The higher the sample density, the larger the range over which we can vary the compressive strength through the liquid content. The role of liquid drainage is explored by comparing samples made using dispersions with the same volume of liquid, but varying the drainage rate. We find that the rate of liquid drainage has a larger impact on the compressive strength than the volume of liquid. We image our samples using uCT scanning and relate the fibre orientation distributions to both the compressive strength of the material and the liquid content of the dispersions. Void size is shown to be similar to the average bubble size of the dispersion from which it was produced. Our samples display an anisotropic response to uniaxial compression when compressed in different directions. We attribute this behaviour to a layering of fibres that occurs during sample production. Increasing the liquid content of the dispersion increases the number of fibres which orientate out of these layers, changing the material?s compressive strength. Using Euler?s formula for buckling we propose an explanation for the observed stress-strain response. We present a case study in which we use the foam-forming technique to create beer coasters from brewers spent grain. We probe our samples for the key requirements of commercial beer coasters, such as the rate of liquid absorption, quantity of liquid absorbed and tensile strength. The experiments show that the spent grain coasters absorb liquid at a faster rate and absorb more liquid during a fixed period of time than the commercial coasters. We conclude our results and, focusing on a theme in which we encourage industry to replace non-sustainable materials with foam-formed fibrous alternatives, we identify and propose a direction for the continuation of the project to further explore and improve typical key material requirements. Experiments on compressive strength, recovery and thermal conductivity are proposed. We also set out the preliminary results of an experiment to measure bubble size from the vibrational response emitted as it ruptures. This is a non-invasive method to measure coarsening and may be useful in an industrial setting.
APPROVED
Keywords: Fibrous Material; Material Properties; Mechanical Stength; Natural FIbres; Foam-forming